Analisis Penerjemahan Metafora: Studi Kasus Metafora Dalam Novel Yukiguni Karya Kawabata Yasunari Dan Terjemahannya Daerah Salju Oleh Ajip Rosidi - Rini Widiarti (Lingua Cultura, 2011)
This study aims to describe the form of metaphorical translation of the source language (SL), Japanese, into the target language (TL), Indonesian, as well as the equivalences in TL. The study also explains any the translation procedures used by the translator to get a natural translation so that the metaphor contained in the target text is able to give the same impression with the original text. Data were collected from the work of Kawabata Yasunari “Yukiguni” Novel and the translation "Daerah Salju" by Ajip Rosidi. Metaphor data were obtained by recognizing the collocation incompatibility of that the referent of a word des not match common sense. The results found are TL metaphors are translated in two forms of metaphor and non metaphor. Forms of non-metaphor are divided into simile and non-figurative expression. The results showed that procedure of modulation translation plays an important role to convey the meaning of TL, especially about viewpoint changes and explicit indication. Viewpoint changes occur on metaphorical imagery while explicit indication occurs at similarity points. Transposition procedure is not only used to generate a natural translation in terms of language but also to divert the message from SL to TL. Noted equvalences are widely used by translators to explain the concept of Japanese culture.